Reliable emotion recognition system based on dynamic adaptive fusion of forehead biopotentials and physiological signals. Issue 2 (November 2015) - Khezri, Mahdi; Firoozabadi, Mohammad; Sharafat, Ahmad Reza
Highlights A new dynamic fusion method for designing an emotion recognition system is proposed. A weight is assigned to each classifier based on its performance. The performance of the classifiers during the training and testing phases is considered. Static weights in varying contexts such as emotions do not produce acceptable results. Dynamic weighting strategy improves the performance of the system considerably.